PRODUCTION SYSTEMS AND BEAN CULTIVARS IN INTERCROPPING WITH MAIZE - COSTA, Denis Santiago da; BARBOSA, Rafael Marani; SÁ, Marco Eustáquio de (Scientia Agraria, 2010)
<span style="line-height: 115%; font-family: "Arial","sans-serif"; background: white; font-size: 8pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">For a better exploitation of the area, the use of culture in intercropping can become a viable alternative to higher profitability, especially in small farms that have small area and can explore the family labor. With the intercropping maize-beans, corn can be used for consumption “in natura” and beans for own consumption or used as seed for the next sowing. Exploring this possibility, an experiment was conducted from May to October 2007, in Selvíria-MS, the objective was to study the effects of intercropping systems involving plant arrangement and size of maize on the performance of four common bean cultivars. The experimental design was a randomized block design with four replications and a factorial 4 x 5 made up of four bean cultivars (Carioca Precoce, Colibri, Rubi, IAC Carioca Eté) and five cropping systems (Single, intercropping of a row of beans between rows of tall maize, a row of beans between the rows of short maize, two rows of beans between rows of tall maize and two rows of beans between the rows of small maize). It was concluded that the productivity was dependent on the intercropping system and also the only bean cultivars differed in yield when grown in the single system or a row of beans between maize stature. The cultivars Carioca Precoce and Rubi were among the best in both systems.